Tinjauan Hukum terhadap Peningkatan Investasi Asing di Indonesia Pasca Berlakunya Undang-undang Cipta Kerja - Maulana, Muhammad Asrul; Aristi, Savira (PROGRESIF: Jurnal Hukum, 2024)
This research aims to analyze the legal products related to the function of the Investment Coordinating Board (BKPM) in Indonesia and how BKPM can assist in increasing foreign investment in the country. This research uses a normative method with a statute approach. The results of this research will evaluate the applicable legal regulations, including regulations on foreign investment and investment permits, as well as the role of BKPM in providing support and coordination for foreign investors. And it will also evaluate the performance of BKPM in increasing foreign investment in Indonesia and provide recommendations for future performance improvement. The results of this analysis are expected to provide useful information for the government, foreign investors, and other parties interested in investing in Indonesia.